Insumos para a elaboração do Cadastro Ambiental Rural (CAR): o caso do município de Augusto Corrêa - PA - SOUZA, Lucas Costa de (2022)
The CAR elaboration process needs vectorial and matrix cartographic bases for an efficient survey of the environmental information of a rural property. This study aims to identify these bases, which we call inputs for the implementation of a GIS, inputs from these Vector and Matrix Layers. As an object of study, the municipality of Augusto Corrêa in Northeast Pará was used as an example for the elaboration of this work. For this, the QGIS software version 3.26.0 'Buenos Aires' was used to assemble the scenario by adding vector data as inputs, ranging from land tenure regularization to the environment, from a first question which ways to acquire this data , such as websites of bodies at federal, state and municipal levels, these inputs would be other registered CARs, Land Regularization, Protection Areas, deforestation information. Each input will be used as a form of organization for the elaboration of a CAR in a safer and better way.